2022
DOI: 10.1108/ecam-01-2022-0059
|View full text |Cite
|
Sign up to set email alerts
|

Client and contractor perspectives on attributes affecting construction quality in a war-affected region

Abstract: PurposeThe poor quality of construction work in war-affected regions is a significant issue. The large-scale destruction to the existing infrastructure from the war necessitates cost and time-efficient delivery of construction projects during and post-war to bring normalcy to affected lives and places. Consequently, there is always a tendency to finish construction projects in the shortest possible time on a limited budget without following the proper quality management processes. However, the poor quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 69 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Naveed and Khan (2022) discovered that project risk management had a significant impact on project success. Zaray et al (2022) revealed that project risk management had a significant effect on project quality. Hoque and Hasan (2022) revealed that project quality success had a significant influence on project risk management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Naveed and Khan (2022) discovered that project risk management had a significant impact on project success. Zaray et al (2022) revealed that project risk management had a significant effect on project quality. Hoque and Hasan (2022) revealed that project quality success had a significant influence on project risk management.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, applying effective risk management techniques to manage risks associated with various construction activities has become imperative for the successful delivery of a project. and Zaray, et al (2022) affirmed that constructions project quality has been identified to be negatively influenced by low-quality materials, lack of auditing, lack of proper supervision, design complexity, design concept among others is some of the common sources of construction defects. Also, constructions project quality is negatively influenced by conflicts between project managers and other outside stakeholders such as sub-contractor and owner, suspending important decisions, unawareness of proper planning tools and techniques by project managers, poor monitoring and feedback tools, negative attitude of project managers and project participants, disorganized resources allocation (Amoah & Sibelekwana, 2023;El Khatib et al, 2023;Hijazi, 2021;Mohammed & Adindu, 2021).…”
Section: Background To the Studymentioning
confidence: 95%
See 1 more Smart Citation